Growth and carcass performance of bull calves born from Hereford, Simmental and Charolais cows sired by Charolais bulls - Kamieniecki, H.; Wójcik, J.; Pilarczyk, R.; Lachowicz, K.; Sobczak, M.; Grzesiak, W.; Błaszczyk, P. (Czech Journal of Animal Science, 2009)
The analysis comprised purebred Charolais bull calves (CH) and crossbred bull calves born from Hereford (CH × HE) and Simmental (CH × SI) cows. Body weights and daily gains were measured in subsequent periods of the experiment and the post-slaughter evaluation was carried out. Carcass lean weight and dressing percentage were evaluated, as well as the lean content of five prime cuts. Total weight of the five prime cuts was measured and its share in the half-carcass weight was determined. The rib-eye area was also measured. The CH × SI crossbreds reached significantly higher body weights at weaning, 210-day body weights and weights at finishing, as well as significantly higher daily gains in all the periods (P < 0.05, P < 0.01) and were characterized by the heaviest carcasses and most cuts, particularly the round. The crossbreds had the highest total weight of five prime cuts and total lean weight, highest weight of the round and lean weight in the round. Other relationships were found analyzing the share of each cut in the carcass. The share of tenderloin and rump in the carcass of CH × SI was significantly lower compared to the purebred bulls (P < 0.01) and CH × HE (P < 0.05). They also had a significantly lower share of the shoulder, shank and shin, as compared to the other groups, as well as a significantly higher (P < 0.05) share of the neck, as compared to the purebred bulls. The purebred bulls also achieved good results and had the highest share of the prime cuts and the largest mean rib-eye area.
Keywords: beef bull calves; crossbreds; body weight; daily gains; carcass performance